2020
DOI: 10.3390/cells9010185
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 Increases GDNF Production by Upregulating the Expression of GDNF and Furin in Human Granulosa-Lutein Cells

Abstract: Glial cell line-derived neurotrophic factor (GDNF) is expressed at a high level in the human ovary and GDNF signaling is involved in the direct control of follicular activation and oocyte maturation. Transforming growth factor-β1 (TGF-β1) plays an important role in the regulation of various ovarian functions. Furin is an intracellular serine endopeptidase of the subtilisin family that is closely associated with the activation of multiple protein precursors. Despite the important roles of GDNF and TGF-β1 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…27 Our previous studies showed that furin is highly expressed in hGL cells and is involved in the processing and secretion of several intraovarian factors, including activin A, TGF-β1, and glial cell line-derived neurotrophic factor. [28][29][30] Furthermore, we have shown that BMP4 and BMP7 upregulate the expression of furin in hGL cells. 31 In human epithelial cells, furin promotes mature BDNF by cleaving pro-BDNF.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…27 Our previous studies showed that furin is highly expressed in hGL cells and is involved in the processing and secretion of several intraovarian factors, including activin A, TGF-β1, and glial cell line-derived neurotrophic factor. [28][29][30] Furthermore, we have shown that BMP4 and BMP7 upregulate the expression of furin in hGL cells. 31 In human epithelial cells, furin promotes mature BDNF by cleaving pro-BDNF.…”
Section: Introductionmentioning
confidence: 83%
“…Previous studies have shown that furin is the corresponding enzyme that processes a variety of cellular factors, including neuropeptides, hormones, growth factors, glycoprotein, receptors, adhesion molecules, and bacterial toxins 27 . Our previous studies showed that furin is highly expressed in hGL cells and is involved in the processing and secretion of several intraovarian factors, including activin A, TGF‐β1, and glial cell line‐derived neurotrophic factor 28‐30 . Furthermore, we have shown that BMP4 and BMP7 upregulate the expression of furin in hGL cells 31 .…”
Section: Introductionmentioning
confidence: 84%
“…Third, zoledronate may lead to upregulation of neurotrophic factors, such as glial cell line-derived neurotrophic factor (GDNF) or insulin growth factor-1 (IGF-1). Different bisphosphonates, including zoledronate, upregulate TGF-beta expression ( Jia et al, 2013 ; Manzano-Moreno et al, 2018 ), and TGF-β1 can increase GDNF production by upregulating GDNF and furin gene expression ( Yin et al, 2020 ). Moreover, GDNF overexpression in neuronal progenitors leads to downregulation of four key enzymes of the cholesterol-synthesis pathway, including farnesyl-diphosphate synthetase, resulting in decreased production of farnesyl-pyrophosphate ( Pahnke et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we failed to detect the mutant homozygous genotype TT, and the lethality was the most likely reason for lack of TT genotype (g.37871539C>T) in all sheep breeds. TGIF1 can negatively regulate TGF-β-activated genes such as SMAD2 and SMAD4 (Hu et al, 2011;Hyman et al, 2003;Wotton et al, 1999), and TGF-β/SMAD signalling plays crucial roles in mediating reproduction (Knight & Glister, 2006;Liu, Chang, Yi, Yao, & Leung, 2019;Rossetti et al, 2020;Yin et al, 2020). For example, the disruption of TGF-β/SMAD signalling can cause reproductive problems (Chand et al, 2007), including sterility (Li et al, 2017).…”
Section: Analysis Of the Association Between Tgif1 And Sf1 Polymorpmentioning
confidence: 99%
“…This suggests that TGIF1 plays a critical role in mammalian reproduction. Studies have also revealed that TGF-β/ SMAD signalling is important in reproductive processes, including in follicular activation (Yin, Chang, Yi, Yao, & Leung, 2020), ovarian follicle development (Knight & Glister, 2006) and oocyte maturation (Yin et al, 2020). Indeed, the inhibition or mutation of key members of the TGF-β/SMAD signalling pathway can cause reproductive problems (Chand, Robertson, Shelling, & Harrison, 2007), including sterility (Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%